BISNIS KELUARGA TANPA “PUTERA MAHKOTA” - Andreas Heryjanto (Journal of Business & Applied Management, 2018)
Business viability is a main goal of family business. However, leaders are usually reluctant to letoff their power, even tend to be in charge beyond the age of retirement. The most fatal consequence ofreluctancy to hand over the leadership to his successor is the occurrence of "Prince Charles Syndrome".Viability of family business requires a mature succession plan, maintaining family harmony, theresponsibility and unity of ownership, and maintaining superior resources. Succession plan becomes acrucial issue in this family business. Succession planning should be a priority, by clarifying who the real"Crowned Prince" appointed to continue the family business. In order for business viability to runningwell, the second generation as a business successor must be well prepared, i.e. the process of the tacitknowledge transfer, the full involvement of the next generation, and the planned regeneration. It isneeded of the willingness and magnanimity of current business owners and leaders to gradually let offbusiness de-facto and de-jure to the "Crowned Prince". With well-prepared succession planning, it willavoid potential prolonged family conflicts.Keywords: Business viability, succession plan, family conflict